Cough and ACE Inhibitors: The Truth Beyond Placebo. Issue 3 (22nd February 2018) - Borghi, Claudio; Veronesi, Maddalena
Abstract : Angiotensin converting enzyme (ACE) inhibitors are extensively used for the prevention and treatment of cardiovascular diseases with a wide range of clinical recommendations. The use of ACE inhibitors can cause the onset of a dry cough, whose prevalence has probably been overestimated because of the lack of adequate control. A correct interpretation of available data requires a careful evaluation of placebo‐controlled studies to definitely assess the rate of the most frequent adverse event of ACE inhibition.